2003
DOI: 10.1515/cclm.2003.223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hyperhomocysteinemia on the Cellular Redox State – Impact on Homocysteine-Induced Endothelial Dysfunction

Abstract: Hyperhomocysteinemia is an independent risk factor for the development of atherosclerosis. An increasing body of evidence has implicated oxidative stress as being contributory to homocysteine's deleterious effects on the vasculature. Elevated levels of homocysteine may lead to increased generation of superoxide by a biochemical mechanism involving nitric oxide synthase, and, to a lesser extent, by an increase in the chemical oxidation of homocysteine and other aminothiols in the circulation. The resultant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 67 publications
2
56
2
4
Order By: Relevance
“…98,99 The resultant increase in levels may in part be counterbalanced by homocysteine-dependent increases in ecSOD. 100 For example, Wilcken et al 101 reported a positive correlation between plasma levels of homocysteine and ecSOD in patients with coronary artery disease, and therapy that lowered plasma homocysteine also decreased ecSOD levels. 101 ecSOD levels were correlated inversely with the incidence of cardiovascular disease in these patients, and risk factors for coronary artery disease, such as male gender and smoking, were associated with decreased levels of ecSOD in a previous study.…”
Section: Homocysteinementioning
confidence: 99%
“…98,99 The resultant increase in levels may in part be counterbalanced by homocysteine-dependent increases in ecSOD. 100 For example, Wilcken et al 101 reported a positive correlation between plasma levels of homocysteine and ecSOD in patients with coronary artery disease, and therapy that lowered plasma homocysteine also decreased ecSOD levels. 101 ecSOD levels were correlated inversely with the incidence of cardiovascular disease in these patients, and risk factors for coronary artery disease, such as male gender and smoking, were associated with decreased levels of ecSOD in a previous study.…”
Section: Homocysteinementioning
confidence: 99%
“…Previous studies by Landmesser et al 2002; and Loscalzo et al (Welch et al 1997;Maytin et al 1999;Forgione et al 2000;Trolliet et al 2001;Nedeljkovic et al 2003;Weiss et al 2003) demonstrate that oxidative stress is an important molecular component of vascular disease, including hypertension and atherosclerosis. Increased understanding of the enzymatic and molecular development of cardiovascular disease may allow for more effective treatment and earlier intervention.…”
Section: Introductionmentioning
confidence: 95%
“…Oxidation of soluble homocysteine to highly insoluble homocystine is the main noticeable biochemical reason raised for various cardiovascular diseases, atherosclerosis, Alzheimer and diabetes [5,8]. GHTHase was characterized in our preliminary studies [3] from Aspergillus flavipes, exhibiting a unique catalytic and biochemical properties comparing to glutathione-s-transferase.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in plasma homo-cysteine may be due to the genetic defects in its catabolizing enzymes or nutritional deficiencies in vitamin cofactors. Recently, homocysteinuria was endorsed as the main risk factor for various cardiovascular diseases such as atherosclerosis, thrombogenicity, mal endothelial function, atherothrombosis, Alzheimer's and diabetics [4][5][6][7][8]. The toxicity of homocystine arises from its strong chemical stability, insolubility, with feasibility of accumulation in small arteries causing atherosclerosis [7,8].…”
Section: Introductionmentioning
confidence: 99%